EFFECT OF PRODUCT, PRICE, PROMOTION, DISTRIBUTION CHANNEL, AND SERVICE QUALITY ON PURCHASE DECISION: (CASE STUDY: MSMEs BRICK CRAFT IN BUNTAGE HAMLET, GIRI SASAK) - Nendy Pratama Agusfianto; Ahmad Bairizki (UIN Mataram, 2021)
This study aimed at investigating the effect of product, price, promotion, distribution channel, and service partially on the purchase decision for brick craft at one of MSMEs named UD Maju Terus in Giri Sasak and to finding out the variabel which having the most dominant effect on the purchase decision. This study used an associative research model. The population in it were all customers of UD Maju Terus. The sampel of this study was as many 60 respondents. The sampel was drawn using purposive sampling technique. The data were gathered by distributing closed questionnaires using Likert scale. They were analysed using multiple liniear regression method. The partial effect were tested by using t-test while the most dominant effect were tested by using Dominant Test (Standardized Coefficient Beta). The result of study tested partially showed that Product (X1), Price (X2). Promotion (X3), Distribution Channel (X4), Service Quality (X5), had significant effects on the purchase decision at UD Maju Terus. This was shown by t-test results where each variabel had a t-count value greater than t-table value. The distribution channel (X4) was the most dominant variable affecting the purchase decision for brick craft at UD Maju Terus, Giri Sasak. The result of the regression equation in this study was Y = 0,0358 + 0,0181 X1 + 0,252 X2 + 0,213 X3 + 0, 284 X4 + 0,165 X5